The impact of VaKE-driven online discussions on critical thinking styles among Chinese undergraduates - Xu, Xiaoshu; Su, Yujie; Zhang, Huanhuan; Lei, Vivian Ngan-Lin; Ye, Xiaofang (Frontiers in Psychology, 2025)
This study examines the impact of VaKE-guided online discussion forums on the critical thinking (CT) styles of 100 undergraduate students in Southeast China, focusing on engagement and information-seeking tendencies. Unlike previous research on VaKE’s impact on CT skills, this study investigates its effect on CT styles. A mixed-methods approach was used, combining the 24-item UFCTI and student reflective diaries. Results showed that the experimental group, engaged in VaKE-guided forums, exhibited improved engagement and information-seeking behaviors, while the control group, using traditional methods, saw a decline. Qualitative data further supported these findings, with students reporting enhanced understanding of social issues and increased cognitive flexibility. Challenges, including insufficient teacher-student interaction, were noted, emphasizing the need for careful facilitation. These findings contribute to the literature on ethical reasoning and CT styles, providing insights for educators seeking to enhance cognitive and moral development in higher education.